Analisis Kontekstual Wasiat Wajibah dalam Ayat Al-Qur'an dan Kompilasi Hukum Islam di Indonesia - Fatawi; Akhmad Dulfikar; Nurul Ma’rifah (Universitas Islam Tribakti Lirboyo Kediri, 2023)
In this research, Article 209 of the Compilation of Islamic Law (CIL) will be examined using the Quran. The question is whether the article is in accordance with the content of Surah Al-Baqarah, verse 180, which serves as the basis of mandatory inheritance. This conformity was examined through the contextual analysis proposed by Al-Balkhi. The terms